Finite Element Analysis of Thermoelastic Fiber-Reinforced Anisotropic Hollow Cylinder with Dual-Phase-Lag Model - Hobiny, A.D.; Abbas, I.A.; Berto, F. (Проблемы прочности, 2018)
In the present paper, we have constructed the equations for generalized thermoelasticity of a fiber-reinforced anisotropic hollow cylinder. The formulation is applied in the context of dualphaselag model (DPL). An application of hollow cylinder is investigated for the outer surface is traction free and thermally isolated, while the inner surface is traction free and subjected to thermal shock. The problem is solved numerically using a finite element method. The results of displacement, temperature and radial and hoop stress are obtained and then presented graphically. Finally, the comparisons are made between the results predicted by the coupled theory (CT), Lord and Shulman theory (LS) and dual-phase-lag model (DPL) in presence (WRE) and absence of reinforcement (NRE). Побудовано рівняння для узагальненої термопружності армованого волокнами анізотропного порожнистого циліндра на основі моделі двофазного запізнювання. Досліджується порожнистий циліндр із теплоізольованою ненавантаженою зовнішньою поверхнею, в той час як ненавантажена внутрішня поверхня піддається тепловому удару. Задачу розв’язано чисельно з використанням методу скінченних елементів. Отримані результати для переміщень, температури, радіальних і колових напружень подано графічно. Проведено порівняння між спрогнозованими результатами за зв’язаною теорією термопружності, теорією Лорда–Шульмана та за моделлю двофазного запізнювання при наявності і відсутності армування. Построены уравнения для обобщенной термоупругости армированного волокнами анизотропного полого цилиндра на основе модели двухфазного запаздывания. Исследуется полый цилиндр с теплоизолированной ненагруженной внешней поверхностью, в то время как ненагруженная внутренняя поверхность подвергнута тепловому удару. Задача решена численно с использованием метода конечных элементов. Полученные результаты для перемещения, температуры, радиальных и окружных напряжений представлены графически. Проведено сравнение между прогнозируемыми результатами по связанной теории термоупругости, теории Лорда–Шульмана и по модели двухфазного запаздывания при наличии и отсутствии армирования.